A new molecular multiplex IgE assay for the diagnosis of pollen allergy in Mediterranean countries: A validation study. Issue 3 (9th October 2018) - Di Fraia, Marco; Arasi, Stefania; Castelli, Sveva; Dramburg, Stephanie; Potapova, Ekaterina; Villalta, Danilo; Tripodi, Salvatore; Sfika, Ifigenia; Zicari, Anna Maria; Villella, Valeria; Perna, Serena; Travaglini, Alessandro; et al.
Summary: Background: The identification of the primary sensitizing pollen is difficult in Southern European patients with Seasonal Allergic Rhinitis (SAR) if sensitized to various pollen sources with overlapping seasonality. A more precise diagnosis is obtained by IgE assays to allergen molecules, currently available as singleplex or microarrays. Objectives: To test the analytical performance of a multi‐parameter immunoblot molecular "Pollen Test" specifically designed to test IgE antibodies to pollen extracts and molecules clinically relevant in Southern Europe. Methods: Sera were obtained from 101 children and 98 adults with SAR and tested with a customized multiplex immunoblot assay (EUROLINE Southern European Pollen Profile [ESEP]; EUROIMMUN AG, Luebeck, Germany) containing a comprehensive panel of allergen extracts and molecules. ESEP's outcomes were then compared in selected sera (ESEP positive to negative = 2:1) with those of singleplex IgE assays (ImmunoCAP; ThermoFisher Scientific, Uppsala, Sweden). For each of the examined reagents, qualitative (sensitivity, specificity, accuracy), semi‐quantitative (classes) and quantitative (Spearman's rank correlation, Bland‐Altmann plots) comparisons were performed. Results: Compared to ImmunoCAP, cumulative ESEP's sensitivity and specificity were 87% (95% CI 84%‐90%) and 88% (83%‐93%) for extracts and 99% (98%‐100%) and 87% (83%‐91%) for molecules. Cohen's kappa coefficients (κC ) ranged for extracts from 0.18 (Pellitory) to 0.50 (Cypress) and for molecules from 0.21 (Ole e 1) to 0.68 (Phl p 7). The quantitative outcomes of the two diagnostic tests were highly correlated, with Spearman's rank correlation coefficients always exceeding 0.80. Bland‐Altmann plots showed a tendency of ESEP to overestimate serum specific IgE levels, when compared to ImmunoCAP. Conclusions and clinical relevance: Sensitivity and specificity of ESEP in testing serum IgE antibodies against pollen allergen extracts and molecules, in Italian patients with SAR, both exceeded 85%. The advantages and limitations of a multiplex customized immunoblot assay, in the routine clinical use of molecular diagnostics in Southern European pollen allergic patients, deserve to be tested.